STRATEGI PENGEMBANGAN BISNIS UMKM DI KOTA MATARAM - Andiana, Baiq Dewi Lita (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to analyze the business development strategies of micro, small, and medium enterprises (MSMEs) in Mataram City using a case study-based approach and thematic analysis tools. Data collection was carried out through interviews with MSME practitioners and local government, specifically the office of cooperatives and MSMEs in Mataram City. The results of the interviews were analyzed using thematic analysis to identify supporting factors, obstacles, and prospects for the development of MSMEs in Mataram City. The research findings indicate that from the perspective of MSME practitioners, access to capital, strategic location, event organization, and bazaars are the main factors supporting the development of MSMEs in Mataram City. However, limitations in capital, ineffective marketing, and a lack of business training have become the main obstacles in the development of MSMEs. Therefore, business digitalization and easier access to capital are the main hopes of MSME practitioners in improving their business competitiveness. Meanwhile, from the perspective of local government, it was found that the government's policies in...supporting MSMEs, facilitating marketing and market access, challenges in the development of MSMEs, the role of the government in innovation and digitalization of MSMEs, as well as the collaboration between the government and the private sector are the main themes in the strategy for developing MSMEs in the city of Mataram. The formulation of the business development strategy for MSMEs in the city of Mataram is to expand access to low-interest capital, increase MSME participation in events and bazaars, strategic location-based marketing strategies, improved financial and marketing literacy, ease of access to assistance programs and business training, optimize digital marketing strategies, broader socialization about access to capital and its procedures, simplify loan requirements for MSMEs, provide financial assistance for MSMEs, enhance training and mentoring on business technology usage, encourage digitalization in financial record-keeping and marketing, facilitate MSMEs in adopting digital technology, optimize the government's role in providing capital assistance, provide clearer information about assistance programs, increase MSMEs' access to business and marketing facilities, digitalization of MSMEs to enhance competitiveness, strengthening the MSME business ecosystem through collaboration among business actors, and encouraging innovation in MSME products and services.